2015
DOI: 10.1016/j.ijpharm.2014.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of glycine particle size by impinging jet crystallization

Abstract: The parameters of crystallization processes determine the habit and particle size distribution of the products. A narrow particle size distribution and a small average particle size are crucial for the bioavailability of poorly water-soluble pharmacons. Thus, particle size reduction is often required during crystallization processes. Impinging jet crystallization is a method that results in a product with a reduced particle size due to the homogeneous and high degree of supersaturation at the impingement point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…The crystal size for Condition 3 was larger than that of Condition 1 and 2 ( Figure 5), which directly came from the different numbers of crystals (with secondary nucleation shut off for all three conditions). For a similar condition in batch cooling crystallization (with initial temperature of 35 • C and final temperature of 20 • C) [59], crystals with an average size of circa 600 µm were generated after 20 min to 6 h [60,61], and here, only 10 min were needed. Although glycine was the compound used here, a similar strategy (e.g., suppressing secondary nucleation) may potentially help generate large crystals of other compounds [62][63][64][65][66][67][68][69][70][71][72].…”
Section: Suppressing Secondary Nucleation For Crystal Growth In Slug mentioning
confidence: 99%
“…The crystal size for Condition 3 was larger than that of Condition 1 and 2 ( Figure 5), which directly came from the different numbers of crystals (with secondary nucleation shut off for all three conditions). For a similar condition in batch cooling crystallization (with initial temperature of 35 • C and final temperature of 20 • C) [59], crystals with an average size of circa 600 µm were generated after 20 min to 6 h [60,61], and here, only 10 min were needed. Although glycine was the compound used here, a similar strategy (e.g., suppressing secondary nucleation) may potentially help generate large crystals of other compounds [62][63][64][65][66][67][68][69][70][71][72].…”
Section: Suppressing Secondary Nucleation For Crystal Growth In Slug mentioning
confidence: 99%
“…Higher sonication intensity and longer sonication time favour the formation of smaller crystals with narrow PSD [20][21][22].Impinging jet crystallization is a relatively new field for the researchers in pharmaceutical manufacturing and industrial crystallization [23]. However, it is proved that this method effectively reduces particle size, as well as it has the potential advantage to produce reproducible products with small average particle size and narrow PSD [24]. The rich solution of the API and the antisolvent flow through two jet nozzles, which are arranged diametrically opposite each other, and it enables the generation of high-intensity micromixing of fluids to achieve high and continual supersaturation before the onset of nucleation at the impinging point [25,26].…”
mentioning
confidence: 99%
“…The previous work is inspiring though some design and operational conditions were not given in details. Other recent research on impinging jet crystallization was from Tari et al and Liu et al Tari et al studied antisolvent crystallization of glycine and found that it produced small crystals with narrow size distribution. In addition to experimental research, there was also work on modelling of impinging jet crystallizers …”
Section: Introductionmentioning
confidence: 99%